Prof. Ahmet Sözen's lecture on Cyprus conflict to AEGEE students (Summer 2010, EMU) - Sözen, Ahmet (EasternMediterranean University (EMU), 2010)
[Abstract Not Available]
Prof. Ahmet Sözen's lecture on Cyprus conflict to Aegee students (Summer 2010, EMU)
Keywords: Cyprus Problem; Cyprus Conflict; Cyprus Issue; Cyprus Question; Cyprus Dispute; Peace Negotiations